Deformed and destructive beings the purpose of horror films - Ochoa, George (McFarland & Company, Inc. Publishers, 2011)
"This critical text proposes that the horror film's primary purpose is to present monsters. These monsters satisfy the audience's desire to know the extremities of being, in particular those beings too fantastic and dangerous to know in real life. The text illuminates many aspects of the horror film genre, including epistemology, ethics, evaluation, history, monster taxonomy, and techniques"--Provided by publisher.